1998
DOI: 10.1080/002075498193390
|View full text |Cite
|
Sign up to set email alerts
|

A Petri net model for the operational design and analysis of segmented flow topology (SFT) AGV systems

Abstract: Designing¯exible manufacturing systems in general, and¯exible material handling system in particular, is a complex problem, typically approached through several stages. Here the focus is on the conceptual design stage during which valid approximation-based methods are needed. The segmented¯ow topology (SFT) AGV systems were developed to facilitate control of complex automated material handling systems. This paper introduces a decomposition method, directly derived from timed Petri nets (TPN) theories, to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Non-availability of any support from Government 10 Cheap labor Rao and Deshmukh (1994) 11 Difficulty in use of automated guided vehicles Shankar and Vrat (1999), Maxwell and Muckstadt (1982), Tanchoco (1984, 1986), Bozer and Srinivasan (1989), Mahadeven and Narendran (1990), Kim and Tanchoco (1991), Langevin et al (1994), Kolen et al (1987), Rajotia et al (1998), Barad and Sinriech (1998), Gaskins and Tanchoco (1987), Bartholdi and Platzman (1989), Tanchoco and Sinreich (1992), Berman and Edan (2002), Vis (2006), Ho and Liu (2006) 12 Non-availability of trained personnel for handling the complex environment of FMS Maffei and Meredith (1994), Rao and Deshmukh (1994) 13 Vendor selection problem in supply of hi-tech equipments Robertson and Gatignon (1986), Rao and Deshmukh (1994), McCutcheon (1993)<...>…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Non-availability of any support from Government 10 Cheap labor Rao and Deshmukh (1994) 11 Difficulty in use of automated guided vehicles Shankar and Vrat (1999), Maxwell and Muckstadt (1982), Tanchoco (1984, 1986), Bozer and Srinivasan (1989), Mahadeven and Narendran (1990), Kim and Tanchoco (1991), Langevin et al (1994), Kolen et al (1987), Rajotia et al (1998), Barad and Sinriech (1998), Gaskins and Tanchoco (1987), Bartholdi and Platzman (1989), Tanchoco and Sinreich (1992), Berman and Edan (2002), Vis (2006), Ho and Liu (2006) 12 Non-availability of trained personnel for handling the complex environment of FMS Maffei and Meredith (1994), Rao and Deshmukh (1994) 13 Vendor selection problem in supply of hi-tech equipments Robertson and Gatignon (1986), Rao and Deshmukh (1994), McCutcheon (1993)<...>…”
Section: Discussionmentioning
confidence: 98%
“…Routing of AGVs involves finding a suitable route, e.g., shortest distance path, shortest time path or minimal energy path for every vehicle from its origin to its destination based on current situation (Daniel 1988). For solving scheduling and routing problems of AGVs, many algorithms have been suggested in the literature, e.g., Egbelu and Tanchoco (1986), Kolen et al (1987), Bartholdi and Platzman (1989), Kaspi and Tanchoco (1990), Kim and Tanchoco (1991), Tanchoco and Sinreich (1992), Lin and Dgen (1994), Langevin et al (1994Langevin et al ( , 1996, Taghaboni and Tanchoco (1995), Akturk and Yilmaz (1996), Klien and Kim (1996), Lee et al (1996), Rajotia et al (1998), Barad and Sinriech (1998) and Qiu and Hsu (2001). Qiu et al (2002) conducted a detailed survey of such algorithms and suggested that the existing work can be classified into four general categories:…”
Section: Scheduling and Routing Algorithms For Agvsmentioning
confidence: 99%
“…Other research work addressed analysing the possible status of the modelling domain such as deadlock (Choi et al 2002, Chin et al 2006, redundant tasks (Choi et al 2002), likely process sequence (Tiwari et al 2001, Chin et al 2006, possible process states (Huang 1992, Barad 1998, Gourgand et al 2003, Morandin and Kato 2005. In this research the sequence of the tokens running through a net should be recorded for detailed analysis.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…Between the ends of two segments, stations are located where loads can be transferred from one AGV to another. Methods to design this kind of layout have been described by Barad and Sinriech (1998) and Sinriech and Tanchoco (1997). Asef-Vaziri and Goetschalckx (2008) develop integer programming models for the simultaneous design of guidepath tracks and locations of pickup and dropoff stations.…”
Section: Introductionmentioning
confidence: 99%